Genome-wide identification and functional analysis of long non-coding RNAs in human endothelial cell line after incubation with PM2.5. (February 2019) - Wang, Yan; Wu, Tianshu; Zou, Lingyue; Xiong, Lilin; Zhang, Ting; Kong, Lu; Xue, Yuying; Tang, Meng
Abstract: Epidemiological studies and experimental research have illustrated that PM2.5 has an association with cardiovascular adverse events. However, the underlying mechanisms are still unknown. Long non-coding RNAs (lncRNAs) have been proposed to take part in diverse diseases. To comprehensively gain insight into the molecular toxicity of PM2.5, expression patterns are analyzed in EA.hy926 cell line through RNAs microarray. A total of 356 lncRNA transcripts are dysregulated in 2.5 μg/cm 2 group, and there are 1283 lncRNAs differentially expressed in 10 μg/cm 2 group. From functional analysis, several lncRNAs may be implicated in the bio-pathways of phagosome, TNF signaling pathway, chemokine signaling pathway and gap junction. Moreover, certain lncRNAs participate in the toxicity of PM2.5 through cis- and/or trans-regulation of their co-expressed genes. Therefore, lncRNAs may be used as new candidate biomarkers and potentially preventive targets in cardiotoxicity of PM2.5. Our study indicates that not limited to transcriptional regulation, post-transcriptional regulation plays a pivotal role in PM2.5-caused toxicity. Highlights: A cluster of RNA transcripts are dysregulated in EA.hy926 cells after exposure of PM2.5. The pivotal bio-pathways induced by PM2.5 are phagosome, gap junction, TNF and chemokine signaling pathway. Several lncRNAs are implicated in cell processes through their cis- and/or trans-regulation of co-expressed genes.